Some Backward in Time Results for Thermoelastic Dipolar Structures - Marin, Marin I.; Abbas, Ibrahim A.; Vlase, Sorin; Craciun, Eduard-Marius (Frontiers in Physics, 2020)
In our study, we define the linear backward in time problem for a thermoelastic body with a dipolar structure. In our first main result, we prove the uniqueness of the solution for this problem. Afterward, the issue of locating solutions of the backward in time problem in time will be approached as a consequence of the uniqueness result. In fact, we address the question of the impossibility of locating the solution of this problem in time.